PENGARUH PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA MELALUI DISIPLIN KERJA KARYAWAN DI PT. PANASONIC GOBEL ECO SOLUTIONS MANUFACTURING INDONESIA PASURUAN ÔÇô JAWA TIMUR - jurnalpps pps; Mochamad Atok Ilah; Indra Prasetyo; Mei Indrawati (Jurnal Manajerial Bisnis, 2020)
This research is entitled "The Effect of Career Development and Compensation on Performance Through Employee Work Discipline at PT. Panasonic Gobel Eco Solutions Manufacturing Indonesia". The purpose of this research is to describe performance, work discipline, career development, and employee compensation in the company, as well as to know and analyze the effect of career development and compensation for employee performance both directly and through work discipline. This research is an explanatory research with a quantitative approach. The population in this research were all employees of PT. PESGMFID totaling138 employees. The number of samples taken was 62 employees using the proportional stratified random sampling technique. Data analysis used was Path Analysis and Sobel Test to test indirect effects. The results showed that career development and compensation affect work discipline; career development, compensation, and work discipline affect performance; Career development and compensation affect performance through work discipline.Keywords: performance, work discipline, career development, compensation